A double-grid gel composite inhibitor for inhibiting spontaneous combustion of coal and preparation method thereof
By preparing a double-mesh gel composite inhibitor, combining hyaluronic acid, polyethylene glycol, epigallocate gallate and modified nanoconcave and concave rock stone, the existing inhibitors are solved in the inhibition of coal spontaneous combustion. The problem of insufficient environmental protection has achieved efficient and environmentally friendly coal spontaneous flame retardant effect.
Patent Information
- Application Number
- CN202310194839.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-28
AI Technical Summary
In terms of inhibiting coal spontaneous combustion, existing inhibitors have problems such as short continuous suppression time, low thermal stability and insufficient environmental protection in inhibiting coal spontaneous combustion, and it is difficult to meet the efficient, clean and environmental protection requirements of modern coal mine fire prevention and extinguishing technology.
The solution polymerization method was used to prepare a double mesh gel of hyaluronic acid (HA) and polyethylene glycol (PEG), and epigallocate gallate (EGCG) was added through graft copolymerization technology, and then modified nanometers were added. Concave and convex rock stone (ATP), forming a double mesh gel composite resistor.
It improves the thermal stability and flame retardant properties of the resistor, extends the suppression time of coal spontaneous combustion, and has good environmental protection performance, and can exert a good flame retardant effect throughout the entire stage of coal spontaneous combustion.
Smart Images

Figure CN116478703B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite inhibitors, in particular to a double-grid gel composite inhibitor for inhibiting spontaneous combustion of coal. Background Art
[0002] The spontaneous combustion of coal is the result of a series of complex physical and chemical processes. In order to inhibit the spontaneous combustion of coal, scholars at home and abroad have developed a variety of fire prevention and extinguishing technical measures, mainly including grouting, spraying inhibitors, using inert gas, and injecting three-phase foam or gel materials. Although these methods have played a key role in ensuring the safe production of coal mines, some technical problems related to them have not yet been resolved.
[0003] The advantages of grouting are that the preparation process of slurry is simple and the cost is low. Moreover, slurry can absorb heat and reduce temperature, isolate oxygen and keep moisture. At the same time, it can cement the roof, reduce the porosity of the goaf, and increase the air leakage resistance. However, the disadvantage is that slurry is easily affected by gravitational potential energy, usually only flows to low-lying areas, and has poor accumulation, so it is not effective in preventing and controlling spontaneous combustion of top coal and coal pillars.
[0004] Inert gas fire prevention and extinguishing technology has been widely used in my country's coal, and the oil-fired DQ-150, DQ-1000 inert gas generators and YZWP-180 inert bubble generators have been developed. Although inert gas has the advantages of suppressing combustion and a wide dispersion range, it is easily affected by airflow and escapes, so it cannot stay in the spontaneous combustion area for a long time to play a suppressive role.
[0005] Three-phase foam has the wrapping properties of solid-phase materials, the heat absorption properties of liquid-phase materials, and the oxygen isolation properties of inert gases. However, the stability of three-phase foam is poor and it is easily affected by ambient temperature and pH. Once it bursts, it will lose its fireproof properties.
[0006] Gel-type fire-fighting materials integrate the sealing and plugging effect of grouting materials, the cooling and flame retardant effect of inhibitors, and the moisturizing performance of three-phase foams, which can play a good role in oxygen isolation and cooling of coal bodies. Wu Huiping et al. prepared a retardant gel made of water glass and accelerator, which has better oxygen isolation, cooling, sealing and windproof effects than ordinary retardants, but it is easy to produce toxic and harmful gases, and its environmental protection needs to be improved.
[0007] At present, the composite of multiple types of inhibitory materials has become the mainstream research trend. Among them, gel materials have good physical effects such as oxygen isolation and cooling in the low-temperature stage of coal spontaneous combustion, and the composite gel obtained after composite processing has better moisture retention and sealing performance, which can play a good inhibitory effect on the low-temperature stage of coal spontaneous combustion, and has a series of advantages such as low cost and easy use. Although physical inhibitors have good moisturizing effects and are relatively cheap, their continuous inhibition time is short, and physical inhibitors hardly undergo chemical changes during the inhibition process, so they cannot completely eliminate the risk of coal spontaneous combustion. Xie Fengcheng's research found through experiments that the inhibitory effect of MgCl2 in each stage is not consistent, and the inhibitory effect is only good in the initial stage.
[0008] In order to increase the duration of composite inhibitors' inhibition of coal spontaneous combustion, two technical means to improve the comprehensive performance of composite inhibitors are to use chemical inhibitors to graft composite gels and to use nanomaterials to copolymerize composite gels. Chemical inhibitors can passivate active functional groups in coal and cut off free radical chain reactions, but the inhibitory effect of chemical inhibitors in the low-temperature stage of coal spontaneous combustion is not significant enough, and its application has certain limitations. Dou Guolan studied the inhibitory effect of catechins and polyethylene glycol, and found that the inhibition efficiency was highest when the inhibitor content was 10%. Nanomaterials have good decomposition and heat absorption characteristics, which can greatly improve the high temperature resistance of composite materials, but nanomaterials are easy to agglomerate. There are still some problems in how to use appropriate methods to composite nanomaterials with other inhibitors.
[0009] The combination of composite gel, chemical inhibitor and nanomaterials forms a composite inhibitor with a physical and chemical synergistic inhibition system, which can combine the advantages of each material and make up for the defects of each material to a certain extent. However, the gel preparation technology is still immature, for example, the monomer activity is low, the reaction speed is slow, resulting in low production efficiency. In addition, the current composite inhibitor still has defects such as low thermal stability and insufficient environmental protection, and cannot meet the requirements of modern coal mine fire prevention and extinguishing technology for high efficiency, cleanliness and environmental protection. Therefore, it is of great significance to prepare a composite inhibitor with good thermal stability, high efficiency and environmental protection, so that it can play a good flame retardant effect in all stages of coal spontaneous combustion, which is of great significance to the prevention and control of coal spontaneous combustion. Summary of the invention
[0010] The present invention provides a method for preparing a double-grid gel composite inhibitor for inhibiting coal spontaneous combustion. Hyaluronic acid (HA) and polyethylene glycol (PEG) are prepared into a double-grid composite gel by solution polymerization, epigallocatechin gallate (EGCG) is grafted and copolymerized with the double-grid composite gel, and modified nano-attapulgite (ATP) is added to prepare a double-grid gel composite inhibitor, so as to enhance the inhibitory effect of the inhibitor on coal spontaneous combustion.
[0011] The composite inhibitor of the invention comprises a physical inhibitor, a chemical inhibitor and a nano flame retardant. According to the mass ratio of hyaluronic acid (HA) / polyethylene glycol (PEG), the amount of the chemical inhibitor is 2%-3%, and the amount of the nano flame retardant is 5%-10%.
[0012] The physical inhibitor is a hyaluronic acid / polyethylene glycol double grid gel.
[0013] The chemical inhibitor is epigallocatechin gallate.
[0014] The nano flame retardant is modified nano attapulgite.
[0015] The present invention provides a method for preparing a double-grid gel composite inhibitor for inhibiting spontaneous combustion of coal, comprising the following steps:
[0016] S1: Nano-attapulgite and ethanol solution are fully mixed at a ratio of 1 to 2: 100 to 110, ultrasonically dispersed for 10 to 15 minutes, silane coupling agent KH-570 is added, stirred continuously at room temperature, and then centrifuged, and dried at 100 to 110° C. for 5 to 6 hours to obtain modified nano-attapulgite (ATP) powder.
[0017] S2: Mix hyaluronic acid and deionized water at a ratio of 1 to 2: 100 to 110, preheat to 70 to 80° C., and add ethylenediamine and carbodiimide under stirring to obtain a modified hyaluronic acid solution.
[0018] S3: mixing the polyethylene glycol solution and deionized water at a ratio of 5-10:100-110, adding succinic anhydride and N-hydroxysuccinimide at room temperature with continuous stirring to obtain an activated polyethylene glycol solution.
[0019] S4: The solutions prepared by S2 and S3 were fully mixed in a volume ratio of 1-2:1-2, and a cross-linking agent MBA was added. After stirring, the mixture was sealed and polymerized for 3-4 hours to obtain a hyaluronic acid / polyethylene glycol (HA / PEG) double-grid gel solution. The HA / PEG double-grid gel powder was obtained after drying at 70-80°C for 12-14 hours.
[0020] S5: Mix HA / PEG double grid gel powder and deionized water in a mass ratio of 2-3:100-110, adjust the neutralization degree to 60%-80% with sodium hydroxide solution, and stir at 60-70°C.
[0021] S6: Take an appropriate amount of epigallocatechin gallate (EGCG) powder, dissolve it in an appropriate amount of deionized water, add initiator potassium persulfate, and stir to obtain a pretreated EGCE solution. Drop it into the HA / PEG double-grid gel solution, and add the crosslinker MBA. After continuous stirring, seal the solution for polymerization to obtain a HA / PEG-EGCG composite inhibitor solution, and dry it at 70-80°C for 12-14 hours to obtain a HA / PEG-EGCG composite inhibitor powder.
[0022] S7: Dissolve the ATP powder prepared in S1 in an appropriate amount of deionized water, perform ultrasonic dispersion for 10 to 15 minutes, and drop it into the solution prepared in S5. Continue stirring and sealing to perform polymerization reaction to obtain a HA / PEG-EGCG-ATP composite inhibitor solution, and dry at 70 to 80°C for 12 to 14 hours to obtain a HA / PEG-EGCG-ATP composite inhibitor powder.
[0023] Furthermore, the volume ratio of the silane coupling agent KH-570 in S1 to the ethanol solution is 2-3%.
[0024] Furthermore, the centrifugal separation speed in S1 is 2000-2100 rpm, the centrifugal force is 390-400 g, and the centrifugal separation time is 10-15 min.
[0025] Furthermore, the mass ratios of ethylenediamine and carbodiimide in S2 to deionized water are 0.15-0.2% and 0.05-0.1%, respectively.
[0026] Furthermore, the mass ratios of succinic anhydride and N-hydroxysuccinimide in S3 to deionized water are 0.5-1% and 1-1.5%, respectively.
[0027] Furthermore, the amount of the cross-linking agent in S4 and S6 and the mass ratio of hyaluronic acid / polyethylene glycol, i.e., MBA:HA / PEG=15-20%.
[0028] Furthermore, the amount of epigallocatechin gallate in S6 and the mass ratio of hyaluronic acid / polyethylene glycol, namely EGCG:HA / PEG=2-3%.
[0029] Furthermore, the amount of the initiator in S6 and the mass ratio of hyaluronic acid / polyethylene glycol, ie, KPS:HA / PEG=1.5-2.5%.
[0030] Furthermore, the amount of ATP powder in S7 and the mass ratio of hyaluronic acid / polyethylene glycol, ie, ATP:HA / PEG=5-10%.
[0031] Furthermore, the polymerization reaction temperature in S6 is 60-70° C., and the polymerization reaction time is 3-4 hours; and the polymerization reaction time in S7 is 3-4 hours.
[0032] Furthermore, the stirring time in S1 is 2 to 3 hours; the stirring time in S2 is 2 to 3 hours; the stirring time in S3 is 1 to 2 hours; the stirring time in S4 is 2 to 3 hours; the stirring time in S6 is 2 to 3 hours; and the stirring time in S7 is 2 to 3 hours.
[0033] The present invention uses hyaluronic acid (HA) and polyethylene glycol (PEG) to polymerize into a double-grid gel, which can improve the moisture retention of the gel, enhance the high temperature resistance, and ensure that it is non-toxic and harmless with good environmental protection performance. The hydroxyl group in the PEG structure can be etherified with the hydroxyl group on the surface of the coal, which can enhance the overall stability of the coal. Epigallocatechin gallate (EGCG) is used for graft copolymerization with the double-grid gel, which can effectively combat free radical activity, passivate free radicals in the coal, have very strong antioxidant activity, and have a strong ability to scavenge oxygen free radicals. Polymer-modified nano-attapulgite (ATP) can effectively enhance the thermal stability and flame retardant properties of the inhibitor, and improve its acid and alkali resistance, corrosion resistance and mechanical properties, and has a good optimization effect on the composite inhibition system.
[0034] The beneficial effects of the above technical solution of the present invention are as follows:
[0035] In the above scheme, hyaluronic acid (HA) and polyethylene glycol (PEG) are made into double-grid composite gel by solution polymerization, and epigallocatechin gallate (EGCG) is used for graft copolymerization with the double-grid composite gel, and then nano-attapulgite (ATP) surface-modified by silane coupling agent KH-570 is added for compounding to obtain a composite inhibitor. The construction of the double-grid gel fully utilizes the advantages of physical inhibitors in water absorption and moisture retention, oxygen isolation and temperature reduction, and destruction of heat storage environment, and combines the good moisture retention properties of natural polymer gels and the excellent bonding properties of synthetic polymer gels, which can play a good inhibitory effect in the low-temperature stage of coal spontaneous combustion; the addition of chemical inhibitors can passivate active groups and eliminate free radicals, which can fully participate in the chemical reaction of coal in the high-temperature stage of coal spontaneous combustion, thereby enhancing the inhibitory effect of the composite inhibitor on coal spontaneous combustion; natural nanomaterials enhance the high temperature resistance of the composite inhibitor, thereby improving the comprehensive prevention and control effect of the composite inhibitor system on the process of coal spontaneous combustion.
[0036] This material solves the shortcomings of most inhibitors on the market, such as single component, low inhibition efficiency, short continuous inhibition time and environmental pollution. It is more versatile in the complex environment underground and is an economical, environmentally friendly and efficient inhibitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 (a) 1k times magnified image of HA powder
[0038] Figure 1(b) 1k times magnified image of HA / PEG powder
[0039] Figure 1 (c) 1k times magnified image of HA / PEG-EGCG powder
[0040] Figure 1 (d) 1k times magnified image of HA / PEG-EGCG-ATP powder
[0041] Figure 2 XRD patterns of three experimental sample powders
[0042] Figure 3 TG-DTG curve of raw coal
[0043] Figure 4 TG-DTG curve of HA resistance sample
[0044] Figure 5 TG-DTG curve of HA / PEG barrier
[0045] Figure 6 TG-DTG curve of HA / PEG-EGCG barrier
[0046] Figure 7 TG-DTG curve of HA / PEG-EGCG-ATP
[0047] Figure 8 XPS spectrum of raw coal
[0048] Fig. 9 XPS spectrum of the barrier sample
[0049] Fig.10 Three-dimensional infrared spectrum of raw coal
[0050] Fig.11 Three-dimensional infrared spectroscopy
[0051] Fig.12 The trend of ether bond peak area changing with temperature
[0052] Fig.13 The peak area of oxygen-containing functional groups changes with temperature.
[0053] Fig.14 The trend of the fat base peak area changing with temperature
[0054] Fig.15 The free hydroxyl peak area changes with temperature DETAILED DESCRIPTION
[0055] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0056] Example 1
[0057] The present invention provides a method for preparing a double-grid gel composite inhibitor for inhibiting coal spontaneous combustion, comprising the following steps:
[0058] (1) 1g of nano-attapulgite was measured and added to 100ml of 90% ethanol solution by volume, and ultrasonically dispersed for 10min. 2ml of silane coupling agent KH-570 was added during stirring, and the modified nano-attapulgite solution was obtained after continuous stirring at room temperature for 2h. The modified nano-attapulgite solution was centrifuged (rotating speed 2000rpm, centrifugal force 390g), and the modified nano-attapulgite was obtained after continuous centrifugation at room temperature for 10min. After filtering off the supernatant in the centrifuge tube, the separated modified nano-attapulgite was placed at 100°C and dried for 5h to obtain the modified nano-attapulgite powder.
[0059] (2) Preheat 100 ml of deionized water to 70° C., then slowly add 1 g of hyaluronic acid powder while stirring, and then add 0.17 g of ethylenediamine and 0.05 g of carbodiimide to the solution. After stirring for 2 h, the modified hyaluronic acid solution is obtained and set aside.
[0060] (3) 100 ml of deionized water was added with continuous stirring at room temperature, and 5 ml of polyethylene glycol solution, 0.97 g of succinic anhydride, and 1.07 g of N-hydroxysuccinimide were added. After stirring for 1 h, an activated polyethylene glycol solution was obtained and set aside.
[0061] (4) Take 80 ml of each of the solutions prepared in (2) and (3), stir at 70°C, add 0.32 g of crosslinker MBA, stir thoroughly for 2 h, seal and polymerize for 3 h to obtain a hyaluronic acid / polyethylene glycol (HA / PEG) double-grid gel solution, dry at 70°C for 12 h, and grind to obtain a HA / PEG double-grid gel powder.
[0062] (5) 2 g of HA / PEG gel was dissolved in 100 ml of deionized water, and the neutralization degree thereof was adjusted to 69% with 10% by mass sodium hydroxide solution, and stirred at 60° C.
[0063] (6) Dissolve 0.059 g EGCG powder in an appropriate amount of deionized water, add 0.049 g initiator potassium persulfate, and stir thoroughly to induce free radical reaction of EGCG. Then drop it into the stirring HA / PEG double grid gel solution, add 0.32 g crosslinker MBA, continue stirring for 2 h, seal and polymerize for 3 h to obtain HA / PEG-EGCG composite inhibitor solution, dry at 70 ° C for 12 h, and grind to obtain HA / PEG-EGCG composite inhibitor powder.
[0064] (7) Take 0.2 g of the modified nano-ATP powder, dissolve it in an appropriate amount of deionized water, ultrasonically disperse it for 10 min, and drop it into the stirring HA / PEG-EGCG solution. After continuous stirring for 2 h, seal the polymerization reaction for 3 h to obtain a HA / PEG-EGCG-ATP composite inhibitor solution, dry it at 70 ° C for 12 h, and then grind it to obtain a HA / PEG-EGCG-ATP composite inhibitor powder.
[0065] Example 2
[0066] In step (5) of Example 1, the neutralization degree of the HA / PEG solution was adjusted to 60% using sodium hydroxide solution and stirred at 60°C.
[0067] In step (6) of Example 1, 0.04 g of EGCG powder was dissolved in an appropriate amount of deionized water, and 0.03 g of initiator potassium persulfate was added, and the mixture was stirred thoroughly to induce a free radical reaction of EGCG.
[0068] The remaining steps are the same as in Example 1.
[0069] Example 3
[0070] In step (5) of Example 1, the neutralization degree of the HA / PEG solution was adjusted to 80% using sodium hydroxide solution and stirred at 60°C.
[0071] In step (6) of Example 1, 0.05 g of EGCG powder was dissolved in an appropriate amount of deionized water, and 0.04 g of initiator potassium persulfate was added, and the mixture was stirred thoroughly to induce a free radical reaction of EGCG.
[0072] The remaining steps are the same as in Example 1.
[0073] The HA / PEG-EGCG-ATP composite inhibitor prepared in Example 1 was used to prepare the inhibited coal sample, and the original coal, HA inhibited coal sample, HA / PEG inhibited coal sample and HA / PEG-EGCG inhibited coal sample were used as the control group to compare the inhibitory effects of each component inhibitor.
[0074] Table 1
[0075] Serial number Inhibiting materials Deionized water Coal Sample Comparative Example 1 - 10ml 10g Comparative Example 2 1.0g HA 10ml 10g Comparative Example 3 1.0g HA / PEG 10ml 10g Comparative Example 4 1.0g HA / PEG-EGCG 10ml 10g Comparative Example 5 (Example 1) 1.0g HA / PEG-EGCG-ATP 10ml 10g
[0076] Comparative Example 1
[0077] Weigh 10.0 g of coal sample and mix it evenly with 10 ml of deionized water. After fully reacting for 24 hours, naturally air-dry it for 48 hours to form a comparative coal sample (raw coal).
[0078] Comparative Example 2
[0079] Weigh 1.0 g HA and 10.0 g coal sample and mix them evenly with 10 ml deionized water. After fully reacting for 24 hours, naturally air-dry for 48 hours to form a HA-impeded coal sample.
[0080] Comparative Example 3
[0081] Weigh 1.0 g HA / PEG and 10.0 g coal sample and mix them evenly with 10 ml deionized water. After fully reacting for 24 hours, naturally air-dry for 48 hours to form a HA / PEG-retarded coal sample.
[0082] Comparative Example 4
[0083] 1.0 g HA / PEG-EGCG and 10.0 g coal sample were weighed and uniformly mixed with 10 ml deionized water. After fully reacting for 24 h, the mixture was naturally air-dried for 48 h to form a HA / PEG-EGCG-retarded coal sample.
[0084] Comparative Example 5 (Example 1)
[0085] Weigh 1.0 g HA / PEG-EGCG-ATP and 10.0 g coal sample and mix them evenly with 10 ml deionized water. After fully reacting for 24 hours, naturally air-dry for 48 hours to form a HA / PEG-EGCG-ATP inhibited coal sample.
[0086] Scanning electron microscopy (SEM)
[0087] In this embodiment, four composite inhibitor powders of HA, HA / PEG, HA / PEG-EGCG and HA / PEG-EGCG-ATP were ground and sprinkled on the conductive glue. After gold spraying, the samples were photographed using a ZEISS EVO 18 material analysis scanning electron microscope to observe changes in the microscopic morphology of the materials.
[0088] Figure 1The microscopic morphology of the composite inhibitor powder under 1k times magnification of the electron microscope is shown in Figure (a). As shown in Figure (a), the microstructure of the HA powder without composite treatment is loose cotton wool, and the cotton wool is interwoven to form a certain spatial pore structure, which also makes the material have a certain water absorption. As shown in Figure (b), the surface of the double grid gel powder formed by the composite of HA and PEG is obviously more compact, indicating that the composite treatment can effectively enhance the strength and toughness of the gel. The surface of HA / PEG is uneven and has some holes, which is very beneficial to increase the contact area between HA / PEG and water molecules, and is very helpful to enhance the water absorption and moisture retention performance of the gel. As shown in Figure (c), after HA / PEG is grafted and copolymerized with the chemical inhibitor EGCG, its surface becomes gully-like and the degree of concavity increases again. In addition, a large number of wrinkles and pores appear on the surface of HA / PEG-EGCG, which are radially divergent, and the size and depth of its pores have been greatly increased. As shown in Figure (d), after HA / PEG-EGCG was polymerized with the nanomaterial ATP, a large number of tiny nanoparticles appeared around the wrinkles and pores on its surface, which fully increased the specific surface area of the composite inhibitor powder particles and further improved the water absorption and moisture retention properties of the composite inhibitor, so that it can exert a better inhibitory effect.
[0089] X-ray diffraction experiment (XRD)
[0090] In this example, three experimental sample powders of ATP, modified ATP and HA / PEG-EGCG-ATP were tested by Ultima IV X-ray diffractometer, and the XRD patterns of the crystal particles of the three experimental samples of ATP, modified ATP and HA / PEG-EGCG-ATP were analyzed by Jade 6.5 software, and various crystal parameters of the crystal particles of the experimental samples were obtained, providing a scientific basis for comprehensive testing of the crystal structure of the experimental samples.
[0091] The XRD spectra of the crystal particles of three experimental samples: ATP, modified ATP and HA / PEG-EGCG-ATP are shown in Figure 2. Figure 2As shown. Compared with ATP and ATP modified by KH-570, the X-ray diffraction pattern of the composite inhibitor HA / PEG-EGCG-ATP powder has changed significantly. From a qualitative perspective, the main diffraction peak and the secondary diffraction peak of the HA / PEG-EGCG-ATP powder are basically shifted to the right, and the peak height and peak area of each diffraction peak are reduced, making the X-ray diffraction pattern smoother, and some new diffraction peaks appear. This is a phenomenon caused by the combination of ATP with different materials due to the composite treatment, which also indirectly verifies the success of the composite processing. From a quantitative perspective, the interlayer spacing of the powder crystals at the main diffraction peak of the HA / PEG-EGCG-ATP powder is 0.103 angstroms smaller than that of the ATP powder. At the same time, the crystallinity of the HA / PEG-EGCG-ATP powder is 50.45%, which is 16.9% lower than that of ATP. For the composite inhibitor particles, a smaller interlayer spacing means that the powder particles are in closer contact and less likely to move. A lower crystallinity indicates that the composite inhibitor is more disordered and has a higher degree of compositeness, thus verifying the success of the composite treatment of the inhibitor material.
[0092] Thermogravimetric analysis (TG) experiment
[0093] Take out about 10mg of the experimental sample and put it into the thermogravimetric analyzer. Set the heating rate to 10℃ / min, the heating range to 20℃ to 700℃, and the air flow rate to 100ml / min. Then turn on the program heating to conduct the thermogravimetric analysis test. Thermogravimetric curves of raw coal and four types of retardant coal samples Figure 3-Figure 7 As shown, the TG and DTG curves in the figure are thermogravimetric curves and differential thermogravimetric curves respectively.
[0094] Using the changing trend of TG curve and DTG curve, the temperatures of 8 main characteristic points in the heating process of coal sample can be analyzed, as shown below. T1: Critical temperature, refers to the first maximum point on the DTG curve starting from room temperature, and also represents the first self-acceleration temperature point in the process of coal oxidation and spontaneous combustion; T2: Dry cracking temperature point, the first minimum point on the TG curve starting from room temperature, this characteristic point represents the temperature at which the weight of the coal sample reaches the minimum value from room temperature; T3: Active temperature, the temperature point corresponding to when the TG curve begins to increase after the dry cracking temperature; T4: Acceleration temperature, refers to the temperature point of the maximum value on the DTG curve before the ignition temperature point of the coal sample; T5: Thermal decomposition temperature, is the corresponding temperature at which the mass of the coal sample reaches the maximum value; T6: Ignition temperature point, is the corresponding temperature at which the mass ratio of the coal sample reaches the maximum value; T7: Maximum weight loss rate temperature point, is the corresponding temperature at which the weight loss rate of the coal sample reaches the maximum value; T8: Burnout temperature point, is the corresponding temperature at which the spontaneous combustion of the coal sample ends.
[0095] The above 8 characteristic point temperatures can divide the spontaneous combustion stage of coal samples into 4 stages, namely, water evaporation and adsorption stage (T1-T2), oxygen absorption and weight gain stage (T2-T5), pyrolysis and combustion stage (T5-T8) and burnout stage (>T8). By analyzing the changes in the temperature of the 8 characteristic points of coal samples before and after the retardant treatment, a more comprehensive quantitative evaluation of each stage of the spontaneous combustion process of coal samples can be carried out, providing an experimental basis for the comprehensive evaluation of the inhibitory performance. The characteristic values of coal samples before and after the retardant treatment in the air atmosphere at a temperature rise of 10°C / min are shown in Table 2.
[0096] Table 2
[0097]
[0098] The 8 characteristic temperature points of HA / PEG-EGCG-ATP are the highest among all experimental samples. Compared with raw coal, the average increase of the 8 characteristic temperature points is 28.15%. Since HA / PEG-EGCG-ATP composite inhibitor combines the advantages of physical inhibitors in moisturizing and cooling, the performance of chemical inhibitors in passivating active groups, and the efficacy of nanomaterials in homogeneous inhibition, it has a triple synergistic composite inhibitor system. Therefore, from the perspective of characteristic temperature, the inhibitory effect of HA / PEG-EGCG-ATP composite inhibitor is the best among all experimental samples.
[0099] X-ray photoelectron spectroscopy experiment
[0100] In this embodiment, an X-ray photoelectron spectrometer is used to test the raw coal and the inhibitory coal samples, and the changes in the occurrence forms of the main elements on the surface of the coal samples before and after the inhibitory treatment are compared.
[0101] The XPS spectra of raw coal and barrier samples are as follows: Figure 8 , Fig. 9 As shown in Table 3, the XPS total spectrum of the raw coal and the barrier sample is shown in Table 3. The surface of the raw coal mainly contains five elements: oxygen, nitrogen, carbon, silicon and aluminum. Among them, the carbon element content is the highest, accounting for 66.20% by weight, followed by the oxygen element content, accounting for 15.67% by weight, and the contents of nitrogen, silicon and aluminum are relatively small. After the barrier treatment, the element composition and content of the barrier surface have changed. The surface of the barrier sample mainly contains six elements: oxygen, nitrogen, carbon, silicon, aluminum and calcium. Among them, the carbon element content is the highest, accounting for 62.76% by weight, which is 3.44% lower than that of the raw coal. The oxygen element content is second, accounting for 16.04% by weight, which is 0.37% higher than that of the raw coal, and the contents of nitrogen, silicon, aluminum and calcium are relatively small. Due to the changes in the element composition and content of the coal sample surface, it can be preliminarily qualitatively judged that the inhibition treatment of the composite inhibitor has a certain impact on the coal sample.
[0102] Table 3
[0103]
[0104] The carbon spectrum, nitrogen spectrum and oxygen spectrum of the raw coal and the impeded coal samples are shown in Table 4. The carbon spectrum parameters show that the weight ratio of CH and CC increases to 1.08% after the impeded treatment, indicating that the impeded sample contains more aliphatic side chains substituted by aromatic rings, with high aromaticity and condensation degree. Some alkyl side chains will be converted into relatively stable ether bonds under oxidation, which helps to improve the stability of the coal sample. From the nitrogen spectrum parameters, it can be seen that whether it is the occurrence form of nitrogen on the surface of the raw coal or the impeded sample, the proportion of pyrrolic nitrogen (N-5) is the highest, and the impeded treatment can effectively reduce the content of pyridinic nitrogen (N-6) in the coal sample. The oxygen spectrum parameters show that the weight ratio of -O- in the impeded sample increases to 0.05% after the impeded treatment. The increase in the ether oxygen content indicates that the impeded treatment can effectively increase the content of stable functional group ether bonds in the coal sample and effectively enhance the stability of the coal sample, which is consistent with the XPS carbon spectrum of the coal sample.
[0105] Table 4
[0106]
[0107] Infrared spectroscopy experiment
[0108] The coal samples were tested using a Fourier transform infrared spectrometer to monitor the changes in the main functional groups in the coal samples in real time. The temperature range was set to 15-300°C, the heating rate was 3°C / min, the scanning range was 650-4000cm-1, the acquisition time was 100min, and the air flow rate was 50ml / min. The three-dimensional infrared spectra of the raw coal and the resistance sample (such as Fig.10 and Fig.11 ), the trend of ether bond peak area changing with temperature (as shown in Fig.12 ), the trend of the peak area of oxygen-containing functional groups changing with temperature (as shown in Fig.13 As shown), the trend of the fatty base peak area changing with temperature (as shown Fig.14 The free hydroxyl peak area changes with temperature (as shown in Fig.15 The inhibition mechanism of the composite inhibitor was obtained through analysis.
[0109] from Fig.12It can be seen that the peak area of ether bonds in the coal samples treated with the inhibitor is higher than that in the raw coal, and as the temperature increases, the ether bond content in the inhibitor increases more rapidly. The increase in the ether bond content is due to the replacement of the hydrogen atoms in the alcohol hydroxyl groups of the coal samples by the alkyl groups in the composite inhibitor, resulting in an etherification reaction. The etherification reaction can block the continued oxidation reaction of the alcohol and produce unstable hydrocarbon intermediates and active free radicals, thereby terminating the process of the oxidation chain reaction, and as the temperature rises, the effect of the etherification reaction to generate ether bonds will be more significant. The increase in the ether bond content shows that the composite inhibitor can effectively improve the stability of the coal molecular structure, thereby effectively inhibiting the spontaneous combustion process of coal.
[0110] from Fig.13 It can be seen that with the increase of temperature, the carbonyl content in coal samples and barrier samples shows an overall upward trend, which indicates that the coal-oxygen complex reaction will become more intense with the increase of temperature, resulting in an increase in the carbonyl content of the intermediate product. Unlike the raw coal, after being treated with the composite inhibitor, the peak area of the carbonyl in the barrier sample is lower than that of the raw coal. In addition, the growth rate of the carbonyl in the barrier sample is lower and the growth trend is slower. This is because the composite inhibitor hinders the contact between coal and oxygen and the evaporation of water, thereby inhibiting the formation of carbonyl in the coal sample, proving that the inhibition treatment can effectively delay the natural oxidation process of coal.
[0111] from Fig.14 It can be seen that with the increase of temperature, the carbonyl content in the coal sample and the barrier sample shows an overall downward trend. This shows that the coal-oxygen complex reaction will become more intense with the increase of temperature. Due to the attack of oxygen molecules, a large number of fatty side chains will break and combine with oxygen to form carbon oxides, thereby causing a significant increase in the consumption rate of fatty groups in coal. After treatment with the composite inhibitor, the peak area of fatty groups in the barrier sample is slightly higher than that of the original coal, which is due to the introduction of the double-grid gel HA / PEG in the composite inhibitor. During the heating process, the consumption rate of fatty groups in the barrier sample is significantly lower than that of the original coal, and the downward trend is slower, which proves that the composite inhibitor has a strong free radical scavenging ability, can effectively inhibit the consumption of fatty groups in coal, and delay the natural oxidation process of coal.
[0112] from Fig.15It can be seen that with the increase of temperature, the free hydroxyl content in the raw coal shows an overall trend of first decreasing, then increasing, and then decreasing. This is because in the low-temperature stage of coal spontaneous combustion, the main reason for the consumption of free hydroxyl is the evaporation of water in the coal. As the temperature rises, the organic components in the coal will undergo a dehydroxylation reaction, thereby generating a large number of free hydroxyl groups and free radicals, resulting in a significant increase in the free hydroxyl content in the coal. In the high-temperature stage of coal spontaneous combustion, the consumption of free hydroxyl is mainly due to its reaction with hydrogen in the aliphatic hydrocarbons in the coal to generate water, resulting in a further decrease in the free hydroxyl content in the coal. Compared with the raw coal, the content of free hydroxyl in the coal sample treated with the composite inhibitor increased in the initial stage, which is caused by the free hydroxyl contained in the nanomaterial attapulgite in the composite inhibitor. Since the composite inhibitor has good water absorption and moisture retention, the rate of decrease of free hydroxyl in the inhibitor sample is significantly lower than that of the raw coal in the low-temperature stage of coal spontaneous combustion. Moreover, as the temperature increases, the composite inhibitor significantly improves the inhibitory effect on the free hydroxyl groups in the coal, accelerating the consumption rate of the free hydroxyl groups in the coal sample. Therefore, after entering the high temperature stage, the content of free hydroxyl groups in the barrier sample is lower than that of the raw coal. The peak area of free hydroxyl groups in the barrier sample after the inhibitor treatment decreased by 18.4% during the heating process, which was significantly greater than that of the raw coal, proving that the composite inhibitor can play a significant passivation role on the active group free hydroxyl groups in the coal, thereby improving the stability of the coal and reducing the spontaneous combustion tendency of the coal.
[0113] In summary, in the low-temperature stage of coal spontaneous combustion, the present invention mainly uses the double-grid gel HA / PEG in the composite inhibitor to play a physical inhibitory role. The double-grid gel HA / PEG can isolate oxygen and destroy the coal-oxygen contact environment. Its good water absorption and moisture retention properties can consolidate the moisture in the coal body. The interwoven double-grid structure effectively improves the thermal stability and mechanical strength of the double-grid gel HA / PEG, and prolongs the continuous inhibition time of the physical inhibitory effect. In addition, the large amount of water carried by the double-grid gel HA / PEG itself can effectively destroy the heat storage environment of the coal body during the evaporation and heat absorption process, inhibit the accumulation of heat in the coal body, and slow down the heating rate of the coal. In the high-temperature stage of coal spontaneous combustion, due to the gradual decomposition of the double-grid gel HA / PEG, the physical inhibitory effect will gradually fail. At this time, the chemical inhibitor EGCG's chemical inhibitory effect begins to gradually become significant, completing the handover of the inhibitory task. The chemical inhibitor EGCG has extremely strong antioxidant properties, can passivate active groups, and eliminate free radicals in coal. At the same time, EGCG can promote the formation of stable product ether bonds in coal and reduce the spontaneous combustion tendency of coal. Nano-attapulgite ATP added to the composite inhibitor can enhance the physical and chemical inhibition of the composite inhibitor, which is mainly reflected in the fact that nano-attapulgite ATP has a homogeneous inhibition effect and good decomposition endothermic performance, and can effectively consume the active group free hydroxyl in coal.
[0114] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A double-grid gel composite inhibitor for inhibiting spontaneous combustion of coal, characterized in that: The composite inhibitor includes a physical inhibitor, a chemical inhibitor, and a nano flame retardant, wherein the physical inhibitor is a hyaluronic acid / polyethylene glycol double grid gel, the chemical inhibitor is epigallocatechin gallate, and the nano flame retardant is a modified nano attapulgite. According to the mass ratio of the chemical inhibitor to the hyaluronic acid HA / polyethylene glycol PEG, the amount of the chemical inhibitor is 2%-3%, and the amount of the nano flame retardant is 5%-10%. The specific steps include: S1: fully mix the nano-attapulgite and ethanol solution at a ratio of 1-2:100-110, perform ultrasonic dispersion for 10-15 min, add silane coupling agent KH-570, continue stirring at room temperature, perform centrifugal separation, and dry at 100-110°C for 5-6 h to obtain modified nano-attapulgite powder ATP; S2: mixing hyaluronic acid and deionized water at a ratio of 1-2:100-110, preheating to 70-80°C, and adding ethylenediamine and carbodiimide under stirring to obtain a modified hyaluronic acid solution; S3: mixing the polyethylene glycol solution and deionized water at a ratio of 5-10:100-110, adding succinic anhydride and N-hydroxysuccinimide at room temperature with continuous stirring to obtain an activated polyethylene glycol solution; S4: the solutions prepared in S2 and S3 were fully mixed in a volume ratio of 1-2:1-2, and a cross-linking agent MBA was added. After stirring, the mixture was sealed and polymerized for 3-4 hours to obtain a HA / PEG double-grid gel solution. The HA / PEG double-grid gel powder was obtained after drying at 70-80°C for 12-14 hours. S5: Mix HA / PEG double grid gel powder and deionized water in a mass ratio of 2-3:100-110, adjust the neutralization degree to 60%-80% with sodium hydroxide solution, and stir at 60-70°C; S6: Take an appropriate amount of epigallocatechin gallate EGCG powder, dissolve it in an appropriate amount of deionized water, add initiator potassium persulfate, stir to obtain a pretreated EGCE solution, drop it into the HA / PEG double grid gel solution, add crosslinker MBA, continue stirring and seal to perform polymerization reaction, obtain HA / PEG-EGCG composite inhibitor solution, and dry at 70-80°C for 12-14h to obtain HA / PEG-EGCG composite inhibitor powder; S7: Take the ATP powder prepared in S1 and dissolve it in an appropriate amount of deionized water, ultrasonically disperse it for 10-15 minutes, drop it into the solution prepared in S5, continue to stir and seal the mouth for polymerization reaction to obtain HA / PEG-EGCG-ATP composite inhibitor solution, and dry it at 70-80°C for 12-14 hours to obtain HA / PEG-EGCG-ATP composite inhibitor powder.
2. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The volume ratio of the silane coupling agent KH-570 in S1 to the ethanol solution is 2~3%.
3. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The centrifugal separation speed in S1 is 2000~2100 rpm, the centrifugal force is 390~400g, and the centrifugal separation time is 10~15min.
4. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The mass ratios of ethylenediamine and carbodiimide in S2 to deionized water are 0.15-0.2% and 0.05-0.1%, respectively.
5. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The mass ratios of succinic anhydride and N-hydroxysuccinimide in S3 to deionized water are 0.5-1% and 1-1.5%, respectively.
6. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The amount of cross-linking agent in S4 and S6 and the mass ratio of hyaluronic acid / polyethylene glycol, i.e., MBA:HA / PEG, are 15-20%.
7. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The amount of epigallocatechin gallate in S6 and the mass ratio of hyaluronic acid / polyethylene glycol, i.e., EGCG:HA / PEG, are 2-3%.
8. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The amount of initiator in S6 and the mass ratio of hyaluronic acid / polyethylene glycol, i.e., KPS:HA / PEG, are 1.5-2.5%.
9. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The amount of ATP powder in S7 and the mass ratio of hyaluronic acid / polyethylene glycol, i.e., ATP:HA / PEG, are 5-10%.
10. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The polymerization reaction temperature in S6 is 60-70°C, and the polymerization reaction takes 3-4 hours; the polymerization reaction in S7 takes 3-4 hours.
11. The method for preparing the double-grid gel composite inhibitor for inhibiting coal spontaneous combustion according to claim 1, characterized in that: The stirring time in S1 is 2~3h; the stirring time in S2 is 2~3h; the stirring time in S3 is 1~2h; the stirring time in S4 is 2~3h; the stirring time in S6 is 2~3h; and the stirring time in S7 is 2~3h.
Citation Information
Patent Citations
Preparation method of hydrogel-based composite inhibitor for coal mine
CN114797693A
Fire preventing and extinguishing composite material for coal mine goaf and preparation method thereof
CN115245646A